2013
DOI: 10.1002/ajp.22154
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Sexual Signaling and Mating Behavior in Olive Baboons (Papio anubis)

Abstract: In primate species, mating decisions seem to be based on multiple signal elements with different roles in the signaling of female reproductive status. Whereas some primate signals are relatively well described (e.g., sexual swellings and copulation calls), studies that simultaneously assess visual, auditory, behavioral, and olfactory cues as signals of reproductive state are rarely undertaken. We used data on variation in sexual behaviors and sexual swellings in relation to the fertile period (estimated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 105 publications
0
37
2
Order By: Relevance
“…Moreover, it is important to note that even within a species, the relationship between female proceptive behaviours and the timing of ovulation may differ, depending on the behaviours of interest. For example, our recent study on olive baboons [22] showed that female approaches contained information on the likely fertile phase, whereas sexual presentations of the anogenital area did not. Moreover, social behaviours in sexual contexts (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Moreover, it is important to note that even within a species, the relationship between female proceptive behaviours and the timing of ovulation may differ, depending on the behaviours of interest. For example, our recent study on olive baboons [22] showed that female approaches contained information on the likely fertile phase, whereas sexual presentations of the anogenital area did not. Moreover, social behaviours in sexual contexts (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…These include skin colour or shape, which may also contain reliable information about the timing of the fertile phase. For example, the size of the swelling in baboons has been found to contain relevant information on the timing of ovulation [10,22], whereas sexual skin colour seems to be uninformative concerning the intra-cycle probability of fertility [16,22]. Besides size and colour, the shape of the swelling may also contain information on female intra-cycle differences in chacma baboons and mandrills [26].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations